2022
DOI: 10.1002/cnm.3575
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate‐based Bayesian calibration of biomechanical models with isotropic material behavior

Abstract: This work introduces a computational methodology to calibrate material models in biomechanical applications under uncertainty. We adopt a Bayesian approach, which estimates the probability distributions of hyperelastic material parameters, based on force‐strain measurements. We approximate the parametric biomechanical model by combining a reduced order representation of the force response with a Polynomial Chaos expansion. The surrogate model allows to employ sampling‐intensive Markov chain Monte Carlo methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The finite element model of the limb and socket used in this study was developed in ABAQUS using an Ogden model (N = 3) model formulation. Similar material laws are often used for describing hyperelastic behaviour in biological materials [43][44][45][46] and other hyperelastic engineering materials, 47,48 including silicone. 49 In a previously published study, we conducted a systematic analysis of the various constitutive laws suitable for modelling the mechanical properties of hyperelastic materials used in this study, and found the Ogden model (N = 3) formulation to offer the best performance.…”
Section: F I G U R Ementioning
confidence: 99%
“…The finite element model of the limb and socket used in this study was developed in ABAQUS using an Ogden model (N = 3) model formulation. Similar material laws are often used for describing hyperelastic behaviour in biological materials [43][44][45][46] and other hyperelastic engineering materials, 47,48 including silicone. 49 In a previously published study, we conducted a systematic analysis of the various constitutive laws suitable for modelling the mechanical properties of hyperelastic materials used in this study, and found the Ogden model (N = 3) formulation to offer the best performance.…”
Section: F I G U R Ementioning
confidence: 99%
“…Generally, local and global sensitivity analysis can be distinguished, we refer to [66] for an overview regarding global sensitivity analysis. Among others the Sobol sensitivity analysis can be used as a global approach, see [62] for a certain application. In contrast, local sensitivity analysis comprises the internal numerical differentiation (IND) and external numerical differentiation (END), [28,29].…”
Section: Identification Proceduresmentioning
confidence: 99%